2022
DOI: 10.9744/jak.24.2.106-116
|View full text |Cite
|
Sign up to set email alerts
|

Women Directors and Firm Profitability: The Role of Corporate Environmental Responsibility Engagement

Abstract: Women in the professional world are still experiencing inequality, discrimination, and obstacles in achieving top management positions. The role of women in improving the com­pany's financial performance is still being debated to this day. This study aims to investigate the role of women directors in 129 manufacturing companies in Indonesia from 2015 to 2019. The data obtained were analyzed using structural equation modelling – partial least square (SEM-PLS). This study found that corporate environmental respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…The increasing interest towards a company will increase profit, which are proxied by ROA (Wicaksono et al, 2023). This result is consistent with research conducted by Fairuzi and Tjahjadi (2022), which shows that companies with good financial performance (ROA) also perform better CSR activities. Thus, it can be concluded that H2 is accepted.…”
Section: Resultssupporting
confidence: 88%
“…The increasing interest towards a company will increase profit, which are proxied by ROA (Wicaksono et al, 2023). This result is consistent with research conducted by Fairuzi and Tjahjadi (2022), which shows that companies with good financial performance (ROA) also perform better CSR activities. Thus, it can be concluded that H2 is accepted.…”
Section: Resultssupporting
confidence: 88%